Cytoreductive treatment in patients with CALR‐mutated essential thrombocythaemia: a study comparing indications and efficacy among genotypes from the Spanish Registry of Essential Thrombocythaemia. (3rd August 2020) - Alvarez‐Larrán, Alberto; Angona, Anna; Andrade‐Campos, Marcio; Soledad Noya, M.; Teresa Gómez‐Casares, M.; Cuevas, Beatriz; Caballero, Gonzalo; García‐Hernández, Carmen; García‐Gutiérrez, Valentín; Palomino, Alicia; Ferrer‐Marín, Francisca; Isabel Mata‐Vázquez, M.; et al.
Abstract: The present study assessed the criteria for initiating cytoreduction and response to conventional therapies in 1446 patients with essential thrombocythemia (ET), 267 (17%) of which were CALR ‐mutated. In low risk patients, time from diagnosis to cytoreduction was shorter in CALR ‐positive than in the other genotypes (2·8, 3·2, 7·4 and 12·5 years for CALR, MPL, JAK2 V617F and TN, respectively, P < 0·0001). A total of 1104 (76%) patients received cytoreductive treatment with hydroxycarbamide (HC) ( n = 977), anagrelide ( n = 113), or others ( n = 14). The estimated cumulative rates of complete haematological response (CR) at 12 months were 40 % and 67% in CALR and JAK2 V617F genotypes, respectively. Median time to CR was 192 days for JAK2 V617F, 343 for TN, 433 for MPL, and 705 for CALR genotypes ( P < 0·0001). Duration of CR was shorter in CALR ‐mutated ET than in the remaining patients ( P = 0·003). In CALR ‐positive patients, HC and anagrelide had similar efficacy in terms of response rates and duration. CALR ‐mutated patients developed resistance/intolerance to HC more frequently (5%, 23%, 27% and 15% for JAK2 V617F, CALR, MPL and TN, respectively; P < 0·0001). In conclusion, conventional cytoreductive agents are less effective in CALR ‐mutated ET, highlighting the need for new treatment modalities and redefinition of haematologic targets for patients with this genotype.